Characterising the digital transformation of IT consulting services–Results from a systematic mapping study. Issue 5 (12th July 2022) - Bode, Meikel; Daneva, Maya; van Sinderen, Marten J.
Abstract: Currently, the digital transformation of the provisioning of IT consulting services to clients forces many companies to reinvent their business models. While the importance of digital transformation is well recognised, very little has been done until now to closely examine the concepts characterising this phenomenon in the domain of IT consulting. This paper aims at mapping out what is currently known in scientific literature about the digitalisation of IT consulting service provisioning and its characterising concepts and approaches. Analysing 20 selected articles, we identified 10 concepts characterising the digital IT consulting and 14 areas considered to be candidates for inclusion in the design of digital IT consulting services. Moreover, we found only one approach to the digitalisation of service provisioning that was empirically evaluated. We conclude that (i) the digital transformation is multifaceted and characterised through many aspects; (ii) digital IT consulting services are primarily explored from business perspective, while research of stakeholders' needs, technical requirements, and designs of relevant artefacts is scarce; (iii) while individual solutions and practices that worked in real‐world contexts are reported, very little empirical evaluation was done. Finally, we reflected on the limitations and on the theoretical and practical implications of this work.